The Effect of Applying Bilimbi Juice (Averrhoa Bilimbi L.) as an Acidifier in Drinking Water on the Quality of Native Chicken Meat - Meisji Liana Sari; Sofia Sandi; Eli Sahara; Arfan Abrar (Journal of Smart Agriculture and Environmental Technology, 2026)
Maintaining animal gut health by applying an acidifier directly impacts the performance of poultry production. This study aimed to determine the effect of adding Bilimbi (Averrhoa bilimbi L.) juice as acidifier to the drinking water of native chickens on meat quality. One hundred one-day old chickens were divided into a completely randomized design (CRD) with 5 treatments and 4 replications. The treatments were a mixture of drinking water and Bilimbi juice (v/v) as follows; P0 (control), P1 (drinking water + 4% Bilimbi juice), P2 (drinking water + 6% Bilimbi juice), P3 (drinking water + 8% Bilimbi juice), and P4 (drinking water + 10% Bilimbi juice) and applied for 60 days. The observed variables were pH, water-holding capacity, cooking-loss water, tenderness, meat fat and cholesterol. The results showed that applying Bilimbi juice up to 10% had no significant effect (P>0.5) on the pH, water holding capacity, cooking loss water, tenderness, fat and cholesterol of native chicken meat.